1996
DOI: 10.1111/j.1432-1033.1996.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Tienilic Acid by Human Yeast‐Expressed Cytochromes P‐450 2C8, 2C9, 2C18 and 2C19

Abstract: Oxidation of tienilic acid by human cytochromes P-450 (CUP) 2C9,2C18, 2C8 and 2C19 was studied using recombinant enzymes expressed in yeast. CYP 2C9 was the best catalyst for 5-hydroxylation of tienilic acid (K, = 5 2 1 pM, k,,, = 1.7 +-0.2 min-I), 30-fold more potent in terms of k,,,/K,,, than CYP 2C18 (K, = 150?15 pM, k,, = 1.850.2min-I) and 300-fold more potent than CYP 2C8 ( K , = 145 +-15 pM, k,,, = 0.2 +-0.1 min-I). CYP 2C19 was unable to catalyze this hydroxylation under our experimental conditions. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…In addition to paclitaxel, 6 substrates hydroxylated by CYP2C8 (17beta-estradiol, 22) fluvastatin acid, 13,23,24) omeprazole, 25,26) rosiglitazone, 27) seratrodast 28) and tienilic acid, [29][30][31] Fig. 5b) were docked into the CYP2C8 model with Gold.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to paclitaxel, 6 substrates hydroxylated by CYP2C8 (17beta-estradiol, 22) fluvastatin acid, 13,23,24) omeprazole, 25,26) rosiglitazone, 27) seratrodast 28) and tienilic acid, [29][30][31] Fig. 5b) were docked into the CYP2C8 model with Gold.…”
Section: Resultsmentioning
confidence: 99%
“…The reactive metabolites generated from these drugs further inactivate their metabolizing enzyme, CYP2C9 (Ló pez- Garcia et al, 1994;Jean et al, 1996;O'Donnell et al, 2003;Hutzler et al, 2009). The metabolic activation mechanism is known to be determined by the structure and substitution pattern on the thiophene ring.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CYP3A4 has been found to metabolize a variety of drugs and itself is inactivated by reactive intermediates (Zhou et al, 2005;Zhou, 2008). CYP2C9 was found to catalyze the metabolic activation of thiophene-containing drugs, such as suprofen and TA, and is inactivated by these drugs via mechanismbased inhibition (López- Garcia et al, 1994;Jean et al, 1996;O'Donnell et al, 2003;Hutzler et al, 2009). The 2,5-diaminothiophene derivative (compound 1) formed GSH conjugates by microsomal enzymes in the presence of NADPH, suggesting that it is an NADPH-dependent oxidative metabolic activation mediated by membrane-bound P450 or FMO enzymes.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that cynomolgus CYP2C18 is functional as a drug-metabolizing enzyme and has substrate selectivity. In humans, CYP2C18 metabolizes CYP2C9 substrates such as torsemide, phenytoin, diclofenac, tienilic acid and tolbutamide [7,8,11,12,24], indicating an overlapping functional property in CYP2C18 and CYP2C9. In cynomolgus macaques, CYP2C43 and CYP2C75, both highly homologous to human CYP2C9, also metabolize Smephenytoin [13,20], suggesting that CYP2C18 also shares a metabolic property in common with other CYP2Cs, CYP2C43 and CYP2C75.…”
mentioning
confidence: 99%